Effects of homocysteine lowering with B vitamins on cognitive aging: meta-analysis of 11 trials with cognitive data on 22, 000 individuals. Issue 2 (25th June 2014) - Clarke, Robert; Bennett, Derrick; Parish, Sarah; Lewington, Sarah; Skeaff, Murray; Eussen, Simone JPM; Lewerin, Catharina; Stott, David J; Armitage, Jane; Hankey, Graeme J; Lonn, Eva; Spence, J David; et al.
ABSTRACT: Background: Elevated plasma homocysteine is a risk factor for Alzheimer disease, but the relevance of homocysteine lowering to slow the rate of cognitive aging is uncertain. Objective: The aim was to assess the effects of treatment with B vitamins compared with placebo, when administered for several years, on composite domains of cognitive function, global cognitive function, and cognitive aging. Design: A meta-analysis was conducted by using data combined from 11 large trials in 22, 000 participants. Domain-based z scores (for memory, speed, and executive function and a domain-composite score for global cognitive function) were available before and after treatment (mean duration: 2.3 y) in the 4 cognitive-domain trials (1340 individuals); Mini-Mental State Examination (MMSE)–type tests were available at the end of treatment (mean duration: 5 y) in the 7 global cognition trials (20, 431 individuals). Results : The domain-composite and MMSE-type global cognitive function z scores both decreased with age (mean ± SE: -0.054 ± 0.004 and -0.036 ± 0.001/y, respectively). Allocation to B vitamins lowered homocysteine concentrations by 28% in the cognitive-domain trials but had no significant effects on the z score differences from baseline for individual domains or for global cognitive function ( z score difference: 0.00; 95% CI: -0.05, 0.06). Likewise, allocation to B vitamins lowered homocysteine by 26% in the global cognition trials but also had no significant effect on end-treatment MMSE-type global cognitive function ( z score difference: -0.01; 95% CI: -0.03, 0.02). Overall, the effect of a 25% reduction in homocysteine equated to 0.02 y (95% CI: -0.10, 0.13 y) of cognitive aging per year and excluded reductions of >1 mo per year of treatment. Conclusion: Homocysteine lowering by using B vitamins had no significant effect on individual cognitive domains or global cognitive function or on cognitive aging.